2013
DOI: 10.1016/j.jtcvs.2012.11.077
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after thoracoabdominal aortic aneurysm repair using hypothermic circulatory arrest

Abstract: Cardiopulmonary bypass with hypothermic circulatory arrest can be safely used for thoracoabdominal aortic aneurysm repair, providing excellent protection against end-organ injury. The early and late mortality rates did not exceed those reported for other open techniques or for endovascular repair, with particularly favorable outcomes among patients undergoing elective repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 9 publications
0
42
0
1
Order By: Relevance
“…Total CPB with an interval of hypothermic circulatory arrest is a widely used technique for operations on the ascending aorta and aortic arch. The main complications of aneurysmal surgery are paraplegia (2-20%) and renal failure (3-14%), both of which are normally avoidable by use of bypass or use of deep hypothermic circulatory arrest [4].…”
Section: Resultsmentioning
confidence: 99%
“…Total CPB with an interval of hypothermic circulatory arrest is a widely used technique for operations on the ascending aorta and aortic arch. The main complications of aneurysmal surgery are paraplegia (2-20%) and renal failure (3-14%), both of which are normally avoidable by use of bypass or use of deep hypothermic circulatory arrest [4].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the rate of paraplegia was only 1% and the rate of stroke was 9%. The largest patient series to date, published in 2013 by Kouchoukos et al ,29 evaluated use of DHCA in 243 patients with TAAAs. Their series showed 7.8% mortality, 5.3% spinal cord ischaemia (3.7% paraplegia), 3.7% stroke and 3.6% renal failure.…”
Section: Recent Therapeutic Developments That Have Improved Outcomesmentioning
confidence: 99%
“…Kouchoukos et al 29 have shown excellent results using this technique and argue, that since hypothermia increases ischaemic tolerance of the visceral organs, there is no need for adjunctive selective perfusion of the kidneys and intestines. The Mount Sinai group has also found that DHCA is effective in reducing the incidence of renovisceral morbidity after TAAA repair 30…”
Section: Recent Therapeutic Developments That Have Improved Outcomesmentioning
confidence: 99%
“…Experienced surgeons and centers report operative mortality rates of 5-8% and paraplegia rates of 3-8% (4)(5)(6)(7). Furthermore, open surgical repair of TAAA is the best option for patients with connective tissue disorders or systemic vasculitis, who are not good candidates for endovascular treatment (8).…”
Section: Introductionmentioning
confidence: 99%